Adiponectin as a sepsis biomarker in dogs: Diagnostic and prognostic value. (8th June 2020) - Torrente, Carlos; Manzanilla, Edgar G.; Bosch, Luis; Villaverde, Cecilia; Pastor, Josep; Ruiz de Gopegui, Rafael; Tvarijonaviciute, Asta
Abstract: Background: Adiponectin (ADPN) is an adipocytokine with insulin‐sensitizing, vascular‐protective, and anti‐inflammatory properties for which concentration changes occur in response to inflammation. Little is known about the regulation of ADPN and the impact of this adipocytokine in septic dogs. Objective: We aimed to assess the diagnostic and prognostic value of ADPN vs other traditional acute‐phase proteins (APPs), such as albumin (ALB), haptoglobin (HPT), fibrinogen (FBG), ferritin (FRT), and C‐reactive protein (CRP) in dogs with naturally acquired sepsis. Methods: This prospective observational study included 20 dogs with sepsis, 27 with low‐grade systemic inflammation (LGSI), and 18 clinically healthy dogs as controls. For method analyses, plasma samples were obtained from all dogs on admission and then every 24‐48 hours until discharge or death in the septic group. Results: Septic dogs had lower ADPN (2.4 ± 0.46 vs 4.5 ± 0.41mg/L, P  < .001) dand ALB (17 ± 1 vs 22 ± 0.8g/L, P  = .002), and tended to have higher CRP (87 ± 4.8 vs 73 ± 4.1mg/L, P  < .079) concentrations than dogs with LGSI on admission. Only ADPN and ALB were able to successfully discriminate animals with LGSI from those presenting with sepsis with areas under the curve (AUCs) for the receiver operating characteristic (ROC) curves of 0.811 and 0.789, respectively. In the septic group, ADPN concentration did not differ between survivors and non‐survivors, either on admission or at discharge or death. Conclusions: Although plasma ADPN can be used as a reliable negative APP in dogs with sepsis, further studies are warranted to confirm the usefulness of this biomarker in terms of disease progression and recovery.